PROFESSIONAL EXAMINATIONS A Department for Students of Accounting. - Chamberlain, Henry T. (The Accounting Review, 1951)
Abstract This article presents questions, prepared by the Board of Examiners of the American Institute of Accountants and were presented as the second half of the November, 1950 Certified Public Accountant. One of the question is, Adams, Baker, Charles and Day are partners. Their interests in the capital and their profit and loss ratios are as follows: Adams's is 40 percent, Baker's is 30 percent, Charles's is 20 percent, Day's is 10 percent. To provide a means whereby the remaining partners might purchase a deceased partner's interest from his estate, a life insurance program was inaugurated whereby life insurance proceeds would be paid to the remaining partners in proportion to their percentage ownership in the partnership. Since each partner was in effect insuring the life of each of the other partners, it was agreed that no partner would pay any part of the premiums on policies covering his own life. One are to prepare the correcting entry that should be made to the partners' capital accounts in order to reflect properly the agreement as to the insurance. Give supporting computations in good form.